A new species of the genus Mesambria Stål, 1878 with notes on the tribe Mesambriini (Orthoptera: Acrididae, Catantopinae) - Storozhenko, Sergey Yu. (Zootaxa, 2018)
The new species Mesambria intermedia Storozhenko, sp. nov. is described from Indonesia. Male genitalia of the type species of the genera Mesambria Stål, 1878 and Traulia Stål, 1873 are described and illustrated for the first time. The diagnosis of the tribe Mesambriini is given and the position of this tribe in the modern classification of grasshoppers is discussed. New synonymy is proposed: Mesambriini Brunner von Wattenwyl, 1893 = Trauliini Bolivar, 1917, syn. nov., = Ranacridinae Xia, 2006, syn. nov.